MCSA/MCSE Implementing, Managing, and Maintaining a Microsoft Windows Server 2003 Network Infrastructure (Exam 70-291) Study Guide and DVD Training System - Shinder, Thomas W. (Syngress Pub., 2003)
Provides coverage of Microsoft Exam 70-291 and features one-of-a-kind integration of text, DVD-quality instructor-led training, and Web-based exam simulation and remediation. This study guide and DVD training system gives students coverage of official Microsoft exam objectives and test preparation.
Print version record
Keywords: Microsoft Windows server -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Microsoft software -- Study guides -- Examinations; Microsoft Windows server; Logiciels Microsoft; Examens; Guides de l'étudiant; Electronic data processing personnel; Certification; Examinations; Microsoft software; Examinations; Study guides